Peran Ibu-Ibu di Lingkungan FKA Dalam Mengelola Keuangan Demi Terwujudnya Generasi Sadar Investasi Dalam Keluarga - Kusumastuti, Anggit Dyah (LPPM Universitas Internasional Batam, 2024)
The importance of investment must be realized by the milennial generation, who incidentally are the young generation who are still productive. By investing, the millennial generation is one step ahead in preparing for their financial stability in the future. Adequate management skills and knowledge of financial literacy have a very important role at a young age. Financial knowledge in the early stages of a career has a very large impact on financial condition and has an impact in the long term. Fostering good financial management in the household through investment activities will produce familiy that are productive and intelligent in financial management according to the priority scale and avoid the lack of knowledge of financial management which has an impact on the difficulty of managing finance.